STUDENTS' WRITING SKILL THROUGH DIARY WRITING TECHNIQUE AT SMA NEGERI 5 KOTA TERNATE - Waode Tiara Kaimudin; Hamida A. Jasin; Muhammad Arif Wicaksono (Jurnal Bilingual, 2023)
The study that aims to determine does the use of diary writing technique can significantly improve students’ writing skills at SMA Negeri 5 Kota Ternate. This study used a quantitative method with a pre-experimental design. The researcher involved 20 students as the sample selected by using the convenient sampling technique. The research instrument was in the form of diary writing of students' personal experiences. The finding shows that diary writing technique at class X (IPA) can significantly improve. It provided the data of the pretest is 60.35 and post-test is 82, 95. It is evident that the result of post-test is higher than pretest. The analysis that the statistical value (4.35) is higher than the t-critical value (1.729) at the significant level of (0.05). This alternative hypothesis (Ha) stating that, diary writing technique improve students’ writing skill at SMA Negeri 5 Kota Ternate is accepted and hypothesis null (Ho) stating that diary writing technique does not improve student writing skill at first year student of SMA Negeri 5 Kota Ternate is rejected. This suggests that the use of this technique is effective to improve student writing skill at SMA Negeri 5 Kota Ternate